IMPLEMENASI MANAJEMEN BERBASIS MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Tommi (UNISAN JURNAL, 2024)
The main problem of this thesis is how to implement madrasa-based management in an effort to improve the quality of education at Di Madrasah Tsanawiyah. to find out efforts to improve the quality of education through the implementation of madrasa- based management at Di Madrasah Tsanawiyah,.This research is a qualitative descriptive research with a normative, sociological, and pedagogical theological approach. The data sources of this research consist of the head of Madrasah, the head of administration, teachers, and employees or staff in Di Madrasah Tsanawiyahas informants. Data collection techniques were carried out using interview instruments, participatory observation, documentation, and reference tracing. The data analysis/processing technique of qualitative data uses 3 stages, namely 1) data reduction, 2) data display, and 3) data verification. The results of the study are First, the steps for implementing madrasa-based management at Di Madrasah Tsanawiyah, namely focusing on planning, organizing, implementing and monitoring management aspects. In terms of planning management, Di Madrasah Tsanawiyahplaces more emphasis on efforts to achieve the mission and vision of the madrasa, Second, Efforts to Improve the Quality of Education through Implementation of Madrasa-Based Management at Di Madrasah Tsanawiyahbased on the author’s findings are the effectiveness of the leadership of the madrasa principal, the effectiveness of planning and development program, effectiveness of teacher and staff discipline, effectiveness of cooperation and partnership with other educational institutions and madrasa-based management of Di Madrasah Tsanawiyah, consisting of internal and external factors. internal factors, namely the principle of help, an easy service system, an effective leadership model.While external factors are community support through the Madrasah committee and government support which provides space for Di Madrasah Tsanawiyahto translate government decisions into more operational decisions, while the inhibiting factor is the curriculum design that has not been carried out by subject teachers. and inadequate resources and inadequate staff development. The implication of this research is that in improving the implementation of madrasa-based management at Di Madrasah Tsanawiyah, education and training activities need to be intensified both in quality and quantity, and need to be continuously motivated and facilitated to be able to participate in them. To raise the spirit of competition among teachers of Di Madrasah Tsanawiyahand all stakeholders through a competition moment for teachers in stages, even if possible they can be included at a higher level, forms of competition that reflect the professional abilities of teachers.